Weathering the Storm : Investing in Port Infrastructure to Lower Trade Costs in East Asia - Abe, Kazutomo (World Bank, 2012)
The world economic crisis of 2008 presents clear challenges to prospects for economic growth in developing countries. This is particularly true for emerging economies in East Asia that have relied to a great extent over the past decade on export-led growth. What steps to facilitate trade promise a relatively strong return on investment for East Asia to help sustain trade and growth? The authors examine how port infrastructure affects trade and the role of transport costs in driving exports and imports for the region. They find that port congestion has significantly increased the transport costs to East Asia from both of the United States and Japan. The analysis suggests that cutting port congestion by 10 percent could cut transport costs in East Asia by up to 3 percent. This translates into a 0.3 to 0.5 percent across-the-board tariff cut. In addition, the estimates suggest that the trade cost reduction of investment in port infrastructure in East Asia that translates into higher consumer welfare would far outweigh the cost for physical expansion of the ports in the region.